2013
DOI: 10.1088/0963-0252/22/6/065004
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the electron energy distribution function of electron beam generated plasmas with molecular gas concentration: I. Experimental results

Abstract: This paper, the first in a series of two, presents experimental results demonstrating the control of electron and ion energy distribution functions in electron beam generated processing plasmas by adding trace concentrations of N 2 to an Ar background. Measurements of the electron energy distribution function, f 0 (E), are performed using a Langmuir probe while measurements of the Ar ion energy distribution function are performed using an energy-resolved mass spectrometer. The experimental results agree with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 21 publications
1
37
1
Order By: Relevance
“…They have demonstrated that the main effect of the external EB was the control of rate constant for ionization, excitation, and momentum transfer. Boris and Petrov et al have written a series of two papers to report the control of the EEPF experimentally and theoretically in EB‐generated plasmas, without any conventionally driving electric field. The ability for control of the EEPF has been demonstrated, by adding small admixture of nitrogen to a background argon gas, at pressure of 25 mTorr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have demonstrated that the main effect of the external EB was the control of rate constant for ionization, excitation, and momentum transfer. Boris and Petrov et al have written a series of two papers to report the control of the EEPF experimentally and theoretically in EB‐generated plasmas, without any conventionally driving electric field. The ability for control of the EEPF has been demonstrated, by adding small admixture of nitrogen to a background argon gas, at pressure of 25 mTorr.…”
Section: Introductionmentioning
confidence: 99%
“…The ability for control of the EEPF has been demonstrated, by adding small admixture of nitrogen to a background argon gas, at pressure of 25 mTorr. A Langmuir probe was employed to measure the EEPF in their experiment . In their theoretical work, a fluid model coupled with the electron Boltzmann equation, was presented to explain the physical mechanisms for the controlling effect of the EEPF to a low energy concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma diagnostic tools were not available in the processing reactor, and so characterizations were performed in two separate reactors. Gas‐phase measurements to determine plasma density were performed in a system described in Boris et al This system utilizes a cylindrical cathode under constant bias to produce e‐beams that run continuously. Langmuir probes were used to determine the plasma density.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…48 Note that Ar +2 ions Figure 12. The Ar +2 ion energy distributions measured in pure and diluted argon.…”
Section: Ion Energy Distributionsmentioning
confidence: 99%